Rester Catholique en France : l'encadrement religieux destiné aux migrants Belgo-Flamands du Lillois, de Paris et des Campagnes Françaises 1850-1960 - Byls, Henk (KADOC studies on religion, culture, and society, 2019)
The rich history of Belgian migration to France“Splendid family. The father, a Flemish, simple, robust guy - the deeply religious mother. The children all bursting with life. They have such courage, to defy the French with their religious conviction. »So spoke the Jesuit father Frans Van den Brande, one of the chaplains of the Flemish peasants of northern France in the interwar period. Its activity had a simple objective: to ensure that Belgian emigrants remained Catholic and Flemish. The initiative was not new. It was part of a long tradition of the Belgian church to continue to concern itself with the fate of their parishioners who had chosen to emigrate to France.What had started as a simple religious framework for emigrants now living in Paris or in the industrial suburbs of Lille, extended after the Great War to the rural regions of northern France. The basis of this commitment was a deep distrust vis-à-vis the host country.Staying Catholic in France explores the nature and effect of these initiatives against the backdrop of the rich history of Belgian migration to France. This story sounds both startling and familiar, dated and yet relevant to today's immigration debate. This work clearly illustrates how strangeness is perceived from minimal differences, but above all how an identity of migrants takes shape from the interactions between country of origin and country of destination.The rich history of Belgian migration in France Staying Catholic in France explores Belgian immigrants in France in their relationship with the Belgian Church. This story sounds both astonishing and relevant in the current debate on migration and clearly illustrates how identity is shaped by minimal perceptions of strangeness.